Political Distrust terhadap Pemerintah pada Masa Pandemik Covid-19: Analisis Perbandingan antara Australia dan Indonesia - Christian, Enrico; Kosandi, Meidi (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
Political trust is important for government in its attempt to implement policies that require the participation of its citizens. During Covid-19 pandemic, trust in government contributes to the decrease of the perception of Covid-19 risks, the increase of public obedience and willingness to do measures of Covid-19 prevention, and the reduction of mortality rate. In regard to this, data show there has been change in the trend of political distrust before and during the Covid-19 in Australia and Indonesia. Using a qualitative approach with data collection methods of library research and online media investigation, this article examines factors that contribute to different trend in political distrust facing Prime Minister Scott Morrison and his government in Australia and President Joko Widodo and his administration in Indonesia before and during Covid-19 pandemic in 2020. Employing Bertsou’s theory of political distrust, this article argues that factors contribute to the different trend in political distrust facing Australia and Indonesia before and during Covid-19 pandemic are the competency of each government in responding to Covid-19 pandemic especially their ability to slow down the spread of Covid-19 and reduce the mortality rate of Covid-19, government’s transparency of Covid-19 data, and the government’s interest.